2017
DOI: 10.1371/journal.pone.0179744
|View full text |Cite
|
Sign up to set email alerts
|

Development of an automated size-based filtration system for isolation of circulating tumor cells in lung cancer patients

Abstract: Circulating tumor cells (CTCs), defined as tumor cells circulating in the peripheral blood of patients with solid tumors, are relatively rare. Diagnosis using CTCs is expected to help in the decision-making for precision cancer medicine. We have developed an automated microcavity array (MCA) system to detect CTCs based on the differences in size and deformability between tumor cells and normal blood cells. Herein, we evaluated the system using blood samples from non-small-cell lung cancer (NSCLC) and small-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 29 publications
4
47
0
Order By: Relevance
“…Therefore, we concluded that MCA system can efficiently capture and detect both epithelial and mesenchymal tumor cells. However, results from our previous studies using MCA system showed that the MCA system tended to miss smaller cells such as small cell lung cancer . Krebs et al also reported that filtration‐based CTC detection was size‐dependent and it may miss cells less than 8 μm in size .…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Therefore, we concluded that MCA system can efficiently capture and detect both epithelial and mesenchymal tumor cells. However, results from our previous studies using MCA system showed that the MCA system tended to miss smaller cells such as small cell lung cancer . Krebs et al also reported that filtration‐based CTC detection was size‐dependent and it may miss cells less than 8 μm in size .…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, AXL‐targeting agents have been developed to overcome drug resistance and their clinical evaluation is ongoing. We previously reported that an automated MCA system with CK staining can efficiently detect CTCs in lung cancer patients compared to the CellSearch system . However, AXL‐expressing CTCs may undergo EMT that cause down regulation of epithelial‐specific marker expression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations